2010
DOI: 10.3923/pjbs.2010.699.705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defoliation and Drought Stress on Yield Components and Chlorophyll Content of Wheat

Abstract: In order to examine the effects of source restriction and drought stress on yield components, flag leaf chlorophyll content and Relative Water Content (RWC) of wheat cultivars, a greenhouse experiment was carried out at Shiraz University, Shiraz, Iran, during 2009-2010. The wheat cultivars including Shiraz, Bahar, Pishtaz, Sistan and Yavaros were sown in 5 kg plastic pots. The source manipulation treatments including control (C), defoliation of all leaves (D1), defoliation of all leaves except the flag leaf (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 11 publications
2
22
0
2
Order By: Relevance
“…Our results were consistent with previous findings [73,83,84] that indicated that there was a linear, positive correlation between chlorophyll content and grain yield. They found that low chlorophyll content caused lower photosynthetic rate and consequently low grain yield.…”
Section: Correlation Among Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with previous findings [73,83,84] that indicated that there was a linear, positive correlation between chlorophyll content and grain yield. They found that low chlorophyll content caused lower photosynthetic rate and consequently low grain yield.…”
Section: Correlation Among Characteristicssupporting
confidence: 93%
“…In fact; TCC is an important factor in determining the photosynthetic rate and dry mater production [73][74][75]. The pronounced effect of water levels on TCC at post-anthesis might be due to the changes in photosynthetic rate, which is parallel to the change of chlorophyll content during grain filling [76].…”
Section: Total Chlorophyll Content (Tcc) and Canopy Temperature Deprementioning
confidence: 99%
“…This reduction may occur due to stress-induced impairment in pigment biosynthetic pathways or in pigment degradation. The decrease in Chl content is a commonly observed phenomenon under drought stress (Bijanzadeh & Emam 2010;Din et al 2011). More decrease in var.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with H 2 O 2 for three days, MsPOD transgenic plants exhibited increased resistance to H 2 O 2 and leaf senescence was delayed ( Figure 4A). Chlorophyll content is also an important factor in the stress responses of plants; plants with high abiotic tolerance have a high chlorophyll content (Sanchez et al, 1983;Bijanzadeh and Emam 2010). We found no significant difference in chlorophyll content between transgenic and WT leaves without H 2 O 2 , but it significantly decreased when treated with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 51%